“Un linguaggio in quanto tecnica del linguaggio”. Sulla teoria del cinema di Pasolini - Mancuso, Francesco (Mechane, 2024)
This paper focuses on the relationship between technique and language, as interpreted by Pier Paolo Pasolini in the mid-1960s. The contribution of technique on language is, in Pasolini, of decisive importance not only on a strictly linguistic level, but also on a socio-political and aesthetic one. Despite being associated with the risk of a potential homologation of language (the emergence of Italian as a national language), the contribution of technology in the years of the Italian “economic miracle” is seen by Pasolini, at the same time, as an opportunity for decisive confrontation and even “salvation” of the language of poetry. The contribution thus seeks to investigate this link through Pasolini’s theory of cinema and with a reference to one of Pasolini’s cinematic experiments in which the author’s metalinguistic and metacinematographic reflection is most evident: Appunti per un’Orestiade africana.